PERBANDINGAN FAKTOR TEKNIS DESAIN KAPAL BANTUAN DENGAN KAPAL LOKAL â‰¤ 5GT DI KABUPATEN CILACAP JAWA TENGAH - Rois Syarif Qoidhul Haq; Mohammad Imron; Budi Hascaryo Iskandar (Bogor Agricultural University, 2020)
Fiberglass aid vessels KM. Nelayan 2018 with a size of â‰¤5 gross tonnage not all can be directly used by local fishermen. Cilacap Regency received 7 aid vessel and it had to renovate. The renovation related to technical design factors, while it is still not yet be reviewed. This study aims to identify and compare differences in technical design factors between the aid vessel and the local vessel. Identification method by direct observation, including measurements of the main dimensions, shape of the hull and bow, general arrangement and working area. The identification data is compared to get the differences. Observation results show that the aid vessel have a ratio of L/D and L/B between local vessel values they are 8,96 from 7,72-9,20 and 13,33 from 12,92-14,11, but have the smallest value at B/D which is 1,49 from 1,51-1,71. The Hulls shape have same type, they are